Poetry and philosophy in the Middle Ages: a festschrift for Peter Dronke - Marenbon, John; Dronke, Peter (Brill, 2010)
This collection of essays, written to honour Professor Peter Dronke on his retirement, addresses the question of the relationship between poetry and philosophy in the Middle Ages
Includes bibliographical references and indexes. - Description based on print version record
Description based on print version record
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002
Keywords: Electronic book; Electronic books -- Criticism, interpretation, etc; Aufsatzsammlung; Bibliografie; Festschrift; Geschichte; Philosophie; Mittelalter; Dronke, Peter; Literatur; Mittellatein